2012
DOI: 10.1113/jphysiol.2012.230425
|View full text |Cite
|
Sign up to set email alerts
|

Differential blood flow responses to CO2 in human internal and external carotid and vertebral arteries

Abstract: Key points• Arterial CO 2 serves as a mediator of cerebral blood flow, and its relative influence on the regulation of cerebral blood flow is defined as cerebral CO 2 reactivity.• Because of methodological limitations, almost all previous studies have evaluated the response of blood flow velocity in the middle cerebral artery to changes in CO 2 as a measure of CO 2 reactivity across the whole brain.• We found that the vertebral artery has lower CO 2 reactivity than the internal carotid artery.Moreover, CO 2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
200
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(222 citation statements)
references
References 50 publications
18
200
3
1
Order By: Relevance
“…Therefore, our study supports earlier physiological reports suggesting regional differences in CO 2 reactivity [16,17]. Nevertheless, both Sato et al [16] and Skow et al [17] used Doppler ultrasound and measured CBF velocity as a surrogate of CBF in healthy subjects.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, our study supports earlier physiological reports suggesting regional differences in CO 2 reactivity [16,17]. Nevertheless, both Sato et al [16] and Skow et al [17] used Doppler ultrasound and measured CBF velocity as a surrogate of CBF in healthy subjects.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, our study supports earlier physiological reports suggesting regional differences in CO 2 reactivity [16,17]. Nevertheless, both Sato et al [16] and Skow et al [17] used Doppler ultrasound and measured CBF velocity as a surrogate of CBF in healthy subjects. Doppler ultrasound as a method to estimate CBF is even more questionable in patients with chronic artery stenosis due to turbulent blood flow in the area of stenosis [7,11,14].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previously, we demonstrated that CO 2 reactivity at ICA was much higher than that at ECA. 31 Similar to this, during heat stress, ICA blood flow would be more influenced by hyperventilation-induced hypocapnia, whereas ECA blood flow might not be influenced largely by hypocapnia. Thus, the regional difference in CO 2 reactivity might affect distribution of these blood flows during heat stress.…”
Section: Modified Blood Distribution In Hyperthermic Conditionmentioning
confidence: 77%
“…Показники цереброваскулярної реактивностi (ЦВР) були отриманi в ходi транскранiального дуплексного сканування судин головного мозку з використанням функцiональних навантажувальних тестiв (ФНТ). Для оцiнки функцiональної спромож-ностi метаболiчного механiзму ауторегуляцiї мозкового кровообiгу застосовувалися проба iз затримкою дихання та проба iз гiпер-вентиляцiєю у каротидному басейнi (у середнiй мозковiй артерiї (СМА)) т а у вертебро-базилярному басейнi (у хребтовiй артерiї у сегментi V 4 (ХА (V 4 ))) [16]. Для оцiнки функцiональної спроможностi мiо-генного механiзму використовувалися орто-статична (вазоконстрикторна реакцiя) i Церебро-васкулярна патологiя займає одну з провiдних позицiй у структурi iнва-лiдизацiї населення як у нашiй країнi, так i у всьому свiтi [11].…”
Section: матерIа л I методиunclassified